2021
DOI: 10.37268/mjphm/vol.21/no.2/art.744
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Health Status Related to Nutritional Status and Development of Children During Lactation Period: A Cross-Sectional Study Among Mothers With Children Age 0 – 6 Months in Agricultural Areas of Indonesia

Abstract: Maternal and child health status (MCHS) plays an essential role in the exclusive breastfeeding practice (EBP), which in turn helps to determine the nutritional status and development of children (NSC & CD) aged 0-6 months. This study aimed to determine the prevalence and factors influencing EBP, NSC, and CD to MCHS in Jember, East Java, Indonesia. A family-based survey was conducted among 470 mothers with children aged 0-6 months, by using a stratified random sampling method. Furthermore, a self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Details about the water consumption of 0-6-month-old babies included the percentage of water intake (%), the volume of daily water consumption, the volume of water consumption in the last 24 hours, and the time of the first intake. The rates of water intake in infants were reported as 44% in 1 -month- olds 40 , 86.2% in 6 weeks-olds 26 , 77% in infants aging 3-months-old 40 , 2.5% in infants aging 4months-old 13 , and 2.5-85% in infants aging 6-months-old 11 , 12 , 26 , 36 , 40 . Moreover, the studies reported that 10% 37 and 96.5% 38 of the 6-month-old babies consumed water in the last 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details about the water consumption of 0-6-month-old babies included the percentage of water intake (%), the volume of daily water consumption, the volume of water consumption in the last 24 hours, and the time of the first intake. The rates of water intake in infants were reported as 44% in 1 -month- olds 40 , 86.2% in 6 weeks-olds 26 , 77% in infants aging 3-months-old 40 , 2.5% in infants aging 4months-old 13 , and 2.5-85% in infants aging 6-months-old 11 , 12 , 26 , 36 , 40 . Moreover, the studies reported that 10% 37 and 96.5% 38 of the 6-month-old babies consumed water in the last 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) 12 / Turkey Descriptive, prospective/ n:355 The aim of this study was to examine the factors leading mothers to discontinue exclusive breastfeeding within the first six months of life. Gender (male/ female) (n) 175/180 Height (cm) (mean ± SD) 50.1±1.2 Weight (g) (mean ± SD) 3201.4±469.2 Head circumference (cm) (mean ± SD) 34.9±0.8 Mother Age (years) (mean ± SD) 28.3±5.2 Delivery method Vaginal/cesarean section (n) 179/176 Breastfeeding at 1-month-old: 68.4 %; Breastfeeding at 4-months-old: 56.5 % Breastfeeding at 6 months-:35.2 % six months: 26 (7.3 %) 8/9 Susanto et al (2021) 13 / Indonesıa Cross-sectional study N: 470 n: 470 Maternal and child health status (MCHS) plays an essential role in the exclusive breastfeeding practice (EBP), which in turn helps to determine the nutritional status and development of children (NSC & CD) aged 0-6 months. This study aimed to determine the prevalence and factors influencing EBP, NSC, and CD to MCHS in Jember, East Java, Indonesia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations